(3GdYHQ hOjhGf GdeHJOC hGdNHQ aj CjGe GdYQH hGdYLe hGdHQHQs - (3YHO GdQMef Hf eMeO Hf eMeO, GHf NdOhf CHh RjO, hdqj GdOjf GdMVQeqj GdETHjdj,J (B808 (3g` s ((3YHO Gddg Hf MSf GdTgjQ HhdO GdaGNhQi s)
(3ChdgG (B:s
(3jHOC HPcQ GdNHQ Yf Ohdg GdSdLhbjI Hbhdg (B: (3bO JbOe dfG Yf PcQ CfSGH GdCee GdcdGe ai fSH GdJQc s
(3BNQgG (B:s
(3GdWHbI GdQGHYI ef GdYQH hge GdeSJYLeg Cgd GdLjd GdfGTF HYO EfbQGV GddSGf GdeUQi hOQhSg hHPcQ CNHGQge fNQL Edi Gd cJGH GdKGdK ef GdJCdja afaQZ HaQGZgG ef GdcJGH s
(3bGd fGSNgG hgh GdCUd GdeYJeO deDdag ef JMHjS GHf NdOhf Ydi NRGfg LGeYI GdbQhjjf HJGQjN (B799 (3hYdjgG NW jOgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B330s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs